Handbook of fiber chemistry - Lewin, Menachem; Pearce, Eli M. (International fiber science and technology series, 1998)
These 12 contributions discuss natural, man-made, and synthetic fibers used for a wide variety of applications throughout the world. The particular fibers discussed are polyester, polyamide, polypropylene, vinyl, wool and mammalian, silk, cotton, rayon, cellulose acetate and triacetate, acrylic, jute and kenaf, and long vegetable. Topics include methods for defining and assessing properties, the role of man-made fibers in fiber spinning technology, and the design of polymer units. Annotation c. by Book News, Inc., Portland, Or.